2003
DOI: 10.1038/sj.ijo.0802304
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conjugated linoleic acid supplementation after weight loss on body weight regain, body composition, and resting metabolic rate in overweight subjects

Abstract: OBJECTIVE:To study the effects of 13 weeks conjugated linoleic acid (CLA) supplementation in overweight subjects after weight loss on weight regain, body composition, resting metabolic rate, substrate oxidation, and blood plasma parameters. DESIGN: This study had a double-blind, placebo-controlled randomized design. Subjects were first submitted to a very-lowcalorie diet (VLCD 2.1 MJ/d) for 3 weeks after which they started with the 13-week intervention period. They either received 1.8 g CLA or placebo per day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
2
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 30 publications
5
70
2
6
Order By: Relevance
“…7,8,12,13 Berven et al 8 found no significant effect on fat mass with a protocol of 3.4 g/day CLA for 12 weeks, although a trend was observed for body fat to decrease with CLA (0.9 kg) and increase with placebo (0.3 kg). In this study, body composition was assessed with BIA, a method that may be less precise in overweight adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,12,13 Berven et al 8 found no significant effect on fat mass with a protocol of 3.4 g/day CLA for 12 weeks, although a trend was observed for body fat to decrease with CLA (0.9 kg) and increase with placebo (0.3 kg). In this study, body composition was assessed with BIA, a method that may be less precise in overweight adults.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, the study length was possibly too short for an effect to be observed. A commonality among the three remaining studies in overweight adults that did not find an effect of CLA on body fat was the inclusion of a weight loss component: Whigham et al 13 included a 12-week very low-calorie diet (VLCD); Kamphius et al 12 utilized a 3-week VLCD; and Atkinson 7 included a diet and exercise regimen during 6 months of treatment. Possibly, the effect of calorie restriction for weight loss in prior studies introduced variability in body weight and body composition change and masked the effect of CLA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies report contradicting results. Although in the majority of them there are no significant differences on body weight, body composition 26 or weight regain 27,28 between controls and CLA-supplemented groups, some studies suggest that CLA might have a tendency to increase lean body mass 27,29,30 . On one hand, one study carried out in overweight/obese adult volunteers 30 report a reduction in body fat mass with doses $3.4 g MI-CLA per day at week 12 (150-580 g more than placebo), with a significant increase in body lean mass in the group that received 6.8 g MI-CLA per day, measured by dual-energy X-ray absorptiometry; however, this group was also the only one with a significant increase in exercise level.…”
Section: Evidence Of Conjugated Linoleic Acid Effects On Body Weight mentioning
confidence: 99%
“…[30][31][32][33] m body lean mass? 27,29,[30][31][32][33] Cis-9,trans-11 CLA m feed efficiency and growth in weanling animals 10,14,[18][19][20] CLA -conjugated linoleic acid. m -increase; k -decrease; ?…”
Section: Evidence Of Conjugated Linoleic Acid Effects On Body Weight mentioning
confidence: 99%